Solve y = 4x - 3 and y = -4x + 5. Use the substitution method.

### 2 Answers | Add Yours

The equations y = 4x - 3 and y = -4x + 5 have to be solved

Substitute y = 4x - 3 in y = -4x + 5

=> 4x - 3 = -4x + 5

=> 8x = 8

=> x = 1

y = 4x - 3 = 4 - 3 = 1

**The solution of the equations is x = 1 and y = 1**

4x-3=-4x+5

4x+4x=5+3

8x=8

x=8/8

x=1

Substitute value of ''x'' in eq.2

y=-4x+5

y=-4(1)+5

y=-4+5

y=1

So,

x=1 and y=1

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes